Translational Authorship and Multilingual (Re)writing in Uljana Wolf and Sophie Seita's Subsisters: Selected Poems (2017). Issue 1 (2nd January 2023) - Codina Solà, Núria
ABSTRACT: As the field of literary studies moves away from national canons, research on multilingual writing tends to focus on the aesthetic features used by multilingual writers to challenge the primacy of the mother tongue. This article complements such accounts by showing that writing across languages has wider implications for literary theory than the questioning of the monolingual paradigm. Multilingualism has the potential to disrupt normative understandings of the literary text as a unique and stable product written by a single author. The article uses Uljana Wolf's multilingual poetry and Sophie Seita's experimental translations in Subsisters (2017) to explore translational authorship as a form of collaborative (re)writing that redefines linguistic and textual ownership as communal, blurring the boundaries between native and foreign language, original and translation. To demystify the idea of the author as an original genius with perfect mastery of language, Wolf's writings simulate translation failure. This practice, which I call pseudomistranslation, invites us to take originality less seriously and to engage with literature in more playful ways.